IMAGE-GUIDED SYNTHESIS REVEALS POTENT BLOOD-BRAIN BARRIER PERMEABLE HISTONE DEACETYLASE INHIBITORS - GANTALA, KALPANA; SREENANCHA, GOVARDHAN (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The blood-brain barrier (BBB) penetration of numerous histone deacetylase (HDAC) inhibitors, which are employed to investigate and treat brain illnesses, has been found to be low in recent research. The high doses required to achieve therapeutic efficacy may be explained by inadequate brain penetrance in addition to the observed low HDAC potency and selectivity. We present here the synthesis and assessment of a new class of highly potent, bloodbrain barrier permeable HDAC inhibitors for central nervous system (CNS) applications, based on an image-guided methodology that involves radiolabeling and parallel synthesis of several compounds based on the benzamide HDAC inhibitor MS-275 as a template. Rapid carbon-11 tagging and PET imaging in the baboon model were used to optimize BBB penetration. The imaging-derived data on BBB penetration from each chemical was then fed back into the design process. After analyzing 17 different compounds, it was discovered that some of them had high binding affinities and BBB permeabilities. A basic benzylic amine was a crucial component in this benzamide series that conferred BBB penetration. The compounds demonstrated an inhibitory effect of 1-100 nM on recombinant human HDAC1 and HDAC2. In the brain, three of the carbon-11 labeled aminomethyl benzamide derivatives demonstrated considerable regional binding heterogeneity (high in the thalamus and cerebellum) and high BBB penetration (∼0.015%ID/cc). When combined, these methods have produced a plan and a forecasting model for creating very strong and BBBpermeable HDAC inhibitors for use in the central nervous system as well as new candidate chemicals for small molecule probes and medications.